2006
DOI: 10.1104/pp.105.076083
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of Plastoglobules in Chloroplasts and Chromoplasts. A Surprising Site for Differential Accumulation of Metabolic Enzymes

Abstract: Plastoglobules (PGs) are oval or tubular lipid-rich structures present in all plastid types, but their specific functions are unclear. PGs contain quinones, a-tocopherol, and lipids and, in chromoplasts, carotenoids as well. It is not known whether PGs contain any enzymes or regulatory proteins. Here, we determined the proteome of PGs from chloroplasts of stressed and unstressed leaves of Arabidopsis (Arabidopsis thaliana) as well as from pepper (Capsicum annuum) fruit chromoplasts using mass spectrometry. Tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
465
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(486 citation statements)
references
References 64 publications
15
465
1
5
Order By: Relevance
“…Among the proteins of the Arabidopsis PG proteome, ABC1-like kinases are among the most abundant Ytterberg et al 2006;Lundquist et al 2012b). Even though little is known about functions of the plastoglobule ABC1-like kinases in plants, the prototypical function of this family is the regulation of ubiquinone metabolism in bacteria and mitochondria (Lundquist et al 2012a).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the proteins of the Arabidopsis PG proteome, ABC1-like kinases are among the most abundant Ytterberg et al 2006;Lundquist et al 2012b). Even though little is known about functions of the plastoglobule ABC1-like kinases in plants, the prototypical function of this family is the regulation of ubiquinone metabolism in bacteria and mitochondria (Lundquist et al 2012a).…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
“…Both were linked to oxidative stress under high light conditions. Thus, the chloroplast localization together with the phenotypes and the analogy to mitochondrial and bacterial ABC1-like kinases suggests that plastoglobule ABC1-like kinase proteins regulate prenylquinone metabolism and that they may do so via phosphorylation of enzymes in the pathway (Ytterberg et al 2006;Lundquist et al 2012a). Indeed, in yeast, it has been demonstrated that ABC1/Coq8 is required for the phosphorylation of Coq3, Coq5 and Coq7, three enzymes involved in ubiquinone pathway.…”
Section: Abc1-like Kinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The proteome of plastoglobules has around two dozen proteins Ytterberg et al 2006;Lundquist et al 2012). These belong to three categories: plastoglobulins/fibrillins (PGL or FBN), plastid metabolic proteins and unclassified proteins.…”
Section: Introductionmentioning
confidence: 99%